Irrigation System through Intelligent Agents Implemented with Arduino Technology - Salazar, Rodolfo; Rangel, José Carlos; Pinzón, Cristian; Rodríguez, Abel (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2013)
The water has become in recent years a valuable and increasingly scarce. Its proper use in agriculture has demanded incorporate new technologies, mainly in the area of ICT. In this paper we present a smart irrigation system based on multi-agent architecture using fuzzy logic. The architecture incorporates different types of intelligent agents that an autonomous way monitor and are responsible for deciding if required enable / disable the irrigation system. This project proposes a real and innovative solution to the problem of inadequate water use with current irrigation systems employed in agricultural projects. This article presents the different technologies used, their adaptation to the solution of the problem and briefly discusses the first results obtained.